Inovasi ICT dalam Pembelajaran Science Interaktif berbantuan Software Lectora Inspire - Azizah, An Nisa Nur; Prafitasari, Aulya Nanda; Eurika, Novy (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to develop an interactive learning medium using Lectora Inspire Software on the topic of ecology and environmental conservation, as well as to examine its validity, practicality, and effectiveness. The research employed the 4-D development model (define, design, develop, disseminate) with a sample of 32 seventh-grade students. The instruments used included validation sheets, student response questionnaires, ICT skills questionnaires, and learning outcome tests. The results revealed that: (1) The interactive learning medium developed with Lectora Inspire was valid, with a Cronbach’s alpha coefficient of 0.91 (very high category); practical, with an average student practicality score of 87% (good category); and effective in improving cognitive learning outcomes, with an N-Gain score of 0.70 (high category). (2) Students’ ICT operational skills reached an average of 89.84% (very good category). Therefore, the media is deemed suitable for use as an alternative learning resource for science education in accordance with the Merdeka Curriculum. It integrates content delivery, practice exercises, and evaluation into a single unified platform, allowing students to learn independently and flexibly.